Frequency of Aspirin Resistance in Ischemic Stroke Patients and Healthy Controls from Colombia. (22nd May 2021) - Roman-Gonzalez, Alejandro; Naranjo, Carlos Andrés; Cardona-Maya, Walter D.; Vallejo, Dionis; Garcia, Francisco; Franco, Cesar; Alvarez, Leonor; Tobón, Luis Ignacio; López, Marta Ibeth; Rua, Carolina; Bedoya, Gabriel; Cadavid, Ángela; et al.
Abstract : Objective . To evaluate the aspirin resistance prevalence in patients with previous ischemic cerebrovascular disease undergoing aspirin therapy for secondary prevention. Materials and Methods . Three hundred fifty patients presenting ischemic strokes and 100 healthy controls under aspirin treatment were evaluated using the optic platelet aggregation test. Results . Aspirin resistance was found in 7.4% of the patients with ischemic stroke and 4% of controls. Aspirin resistance was associated with stroke recurrence in univariate analysis (p = 0.004 ). Aspirin resistance was not associated with smoking, diabetes, or hypercholesterolemia. Conclusion . Aspirin resistance is present in Colombian patients with ischemic stroke as well as in healthy controls.